2016
DOI: 10.1186/s12967-016-0935-4
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-like vesicles in uterine aspirates: a comparison of ultracentrifugation-based isolation protocols

Abstract: BackgroundUterine aspirates are used in the diagnostic process of endometrial disorders, yet further applications could emerge if its complex milieu was simplified. Exosome-like vesicles isolated from uterine aspirates could become an attractive source of biomarkers, but there is a need to standardize isolation protocols. The objective of the study was to determine whether exosome-like vesicles exist in the fluid fraction of uterine aspirates and to compare protocols for their isolation, characterization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 59 publications
0
54
0
1
Order By: Relevance
“…Cervicovaginal lavage EVs and exRNPs, like EVs in the uterus [62,63], may offer information about the health of the reproductive tract and may also facilitate or block transmission of infectious agents. Proteomic analyses of human [64] and rhesus macaque [65] CVL have suggested a core proteome and a highly variable proteome that responds to changes in pregnancy status, menstruation, infection, and other stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Cervicovaginal lavage EVs and exRNPs, like EVs in the uterus [62,63], may offer information about the health of the reproductive tract and may also facilitate or block transmission of infectious agents. Proteomic analyses of human [64] and rhesus macaque [65] CVL have suggested a core proteome and a highly variable proteome that responds to changes in pregnancy status, menstruation, infection, and other stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles have been identified in uterine fluid during the estrous/menstrual cycles in a number of species, including humans, sheep, and mice [1820, 22]. Their release from endometrial epithelial cells in culture [18, 121123] indicates the luminal/glandular epithelium as their source.…”
Section: Extracellular Vesicles In the Uterine Microenvironmentmentioning
confidence: 99%
“…Growing interests in extracellular miRNAs have led to the speculation of whether endometrium is able to secrete miRNAs. Studies have confirmed that miRNAs are encapsulated within EVs in ULF and uterine aspirates in human [ 84 ], sheep [ 22 ], and pigs [ 54 ]. Immunostaining results of membrane markers of exosomes in vivo highlighted an increased secretion trend in both luminal and glandular epithelial cells across the menstrual cycle, and the secretion reached a peak during WOI [ 85 ].…”
Section: Mirnas Participate In Embryo Implantationmentioning
confidence: 99%